(untitled) (Research, Society and Development, 2024)
Objective: To map and analyze the evidence available in the existing literature on the effectiveness and safety of the use of Cannabis sativa in the treatment of Non-Motor Symptoms (NMS) of Parkinson’s Disease (PD). Methodology: This is a scoping review, with a search done in the BVS Direct, EBSCO, Embase, PubMed, and Scopus databases, with no time or language limits. This process was guided by the research question “What is the evidence of the effectiveness and safety of the therapeutic use of Cannabis sativa in the treatment of non-motor symptoms in patients with Parkinson’s Disease?”. Results: Of the 2193 articles found, 90 studies were considered eligible. The studies indicated that Cannabis sativa has the potential to treat various NMS, with significant improvement in pain and sleep disturbances, as well as improvement in neuropsychiatric manifestations and quality of life. Side effect rates tend to be low and, are, generally classified as mild and well tolerated. However, results vary depending on the dose used, how the product is administered, and the cannabinoid compound used, and further studies are needed to assess its effectiveness and safety. Conclusion: The use of Cannabis sativa can improve NMS, with the potential to impact the quality of life of PD sufferers. However, more studies are needed to ensure the effectiveness and safety of this complementary therapy.